Implementation of Card Playing and Journaling Interventions in Schizophrenia Patients with Grandiose Delusions in a Mental Hospital - Chaimira, Sausandha Yasma; Maulana, Indra; Widianti, Efri (Utami Publisher, 2026)
Schizophrenia is a psychological disorder characterized by fragmented thinking, perception, and cognitive function. One common symptom that often appears in schizophrenia patients is delusion. Delusion is a condition where the sufferer cannot distinguish real events from events that occur in their mind. Treatment of delusions can be done through non-pharmacological therapies such as card playing therapy and journaling. This study aims to evaluate the application of card playing and journaling interventions as non-pharmacological interventions in training reality orientation in delusions and improving the social functioning of schizophrenia patients. The research method used is a clinical case report conducted from May 29, 2025 - June 5, 2025, with the subject of a 21-year-old man with a medical diagnosis of schizophrenia. The intervention was carried out over four consecutive meetings with a duration of 15-30 minutes, using card games to match colors and numbers, followed by journaling activities as self-reflection. The evaluation results showed a decrease in the intensity of grandiose delusions characterized by increased concentration during activities and an increase in the patient's ability to control behavior and speak more in accordance with reality. Card-playing interventions help patients practice concentration and following rules, while journaling helps identify unrealistic thoughts and transform them into more rational statements. While complete recovery is not yet achieved, these interventions can have a positive therapeutic impact on patients when combined with pharmacological interventions and other supportive factors.